2008
DOI: 10.1111/j.1365-2893.2008.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal triglyceride transfer protein (MTP) –493G/T gene polymorphism contributes to fat liver accumulation in HCV genotype 3 infected patients

Abstract: (A) A reduced activity of microsomal triglyceride transfer protein (MTP), a key enzyme of assembly/secretion of lipoproteins, is related to HCV steatosis. Host genetic background may influence development of steatosis. The aim of the study was to investigate the association between MTP-493 G/T gene polymorphism, fat liver accumulation and fibrosis progression in HCV infected patients. A total of 102 naïve patients with liver biopsy proven chronic hepatitis C were evaluated for MTP-493 G/T gene polymorphism, HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 34 publications
4
33
0
10
Order By: Relevance
“…However, in chronic HCV infection, the T allele is associated with decreased MTTP expression, which may occur either through a direct binding of some HCV proteins at the Ϫ 493 site or through an upregulation of MTTP-suppressor(s) by HCV ( 179 ). There is also an association between Ϫ 493T and hepatic steatosis in both HCV genotype 3-and nongenotype 3-infected patients ( 180,181 ). Increased lipid droplet accumulation in hepatocytes may provide a safe environment for HCV latency ( 179 ).…”
Section: Mttpmentioning
confidence: 93%
“…However, in chronic HCV infection, the T allele is associated with decreased MTTP expression, which may occur either through a direct binding of some HCV proteins at the Ϫ 493 site or through an upregulation of MTTP-suppressor(s) by HCV ( 179 ). There is also an association between Ϫ 493T and hepatic steatosis in both HCV genotype 3-and nongenotype 3-infected patients ( 180,181 ). Increased lipid droplet accumulation in hepatocytes may provide a safe environment for HCV latency ( 179 ).…”
Section: Mttpmentioning
confidence: 93%
“…Hypobetalipoproteinemia, reduced activity of MTP with negative correlation to hepatic steatosis and viral load, is observed in HCV-G3 chronic infection [11]. Secretion of apoB-100 was reduced by HCV nonstructural proteins using the HCV subgenomic replicon expression system and interaction between the HCV NS5A and apoB-100 was observed [12].…”
Section: Introductionmentioning
confidence: 97%
“…Zampino et al revealed that the presence of T allele in the −493G/T polymorphism of microsomal triglyceride transfer protein (MTP) gene reduces the activity of this key enzyme of assembly/secretion of lipoproteins and predisposes patients infected with HCV genotype 3 to develop higher degree of fatty liver accumulation [140]. Moreover, the SNP rs738409 of adiponutrin/patatin-like phospholipase domain-containing 3 (PNPLA3), which encodes for the I148M protein variant, has been recognized as a determinant of liver fat content.…”
Section: Epidemiology Research Internationalmentioning
confidence: 99%